Impacts of medications on male fertility - Drobnis, Erma Z.; Nangia, Ajay K. (Springer, 2018)
"The over-arching goal of this volume is to help infertility practitioners evaluate and manage their patients with poor semen quality. The authors review the existing literature on the effects of medications on male fertility, and provide detailed information about what is known, giving the number of individuals and population characteristics for studies of medication effects on male fertility. Medications are designed to treat illness and reduce symptoms, but all have undesirable adverse effects such as headache or stomach upset. Some adverse reactions can even be life-threatening, so it is no surprise that some drugs have negative effects on male reproduction. Medical practitioners rarely consider a man's reproductive plans when prescribing medications. Men are routinely treated with drugs that can impair or abolish fertility. Although practitioners in the field of reproductive medicine generally realize that certain drugs impact negatively on reproductive health, there are limited resources providing evidence-based knowledge useful in counseling patients. Tables throughout this volume summarize the information for each drug, providing a handy reference for clinical use"--Publisher's description.
Keywords: Fertility, Human -- Handbooks, manuals, etc.; Male reproductive health.; elektronické knihy; electronic books